2D:4D index in the detection and identification of talent for track and field (Impetus, 2021)
The 2D: 4D digital length index, a supposed marker of androgens in the intrauterine phase, marks differences in muscle mass and sports fitness. Objective. Establish parameters of the 2D: 4D index for the detection and identification of talents for athletics. Materials and methods. Quantitative, observational, prospective study, with a descriptive and relational scope, cross-sectional. 317 athletes (170 men) with a mean age of 24.3 ± 9.4, between 14.1 and 65.9 years, were evaluated in the U-18 World Athletics Championships, Cali 2015, National Games, National University Games, championships national, international events and concentration and training sites. The length of the index and ring fingers of both hands was measured with digital Sata calipers (precision 0.1 mm). The distribution, association, central tendency and dispersion measures were calculated with the SPSS program. It had the endorsement of the bioethics committee. Results. The 2D: 4D index of the right hand was 0.947 ± 0.04 in men and 0.954 ± 0.04 in women; for the left hand it was 0.963 ± 0.04 in men and 0.969 ± 0.04 in women. By areas of athletics as a function of sex, no significant differences were found. Conclusions. The 2D: 4D ratio of the right hand was consistently lower than that of the left hand and was found to be a better predictor of talent. The 2D: 4D index is useful, valid and reliable to identify talents for athletics, especially in aerobic endurance and strength-speed disciplines, as it is a stable, easy and inexpensive characteristic to measure.
Keywords: 2D/4D; 2D:4D; athletics; sports talent; talent detection; talent identification